2022
DOI: 10.1145/3512982
|View full text |Cite
|
Sign up to set email alerts
|

Working for the Invisible Machines or Pumping Information into an Empty Void? An Exploration of Wikidata Contributors' Motivations

Abstract: Structured data peer production (SDPP) platforms like Wikidata play an important role in knowledge production. Compared to traditional peer production platforms like Wikipedia, Wikidata data is more structured and intended to be used by machines, not (directly) by people; end-user interactions with Wikidata often happen through intermediary "invisible machines." Given this distinction, we wanted to understand Wikidata contributor motivations and how they are affected by usage invisibility caused by the machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Working on Wikidata, for example, is constrained by database and ontology logics. In contrast, Wikipedia work “is constrained by meeting Wikipedia’s standards for formatting, quality, notability, neutrality, citations, etc., and the results are viewed primarily by humans” (Zhang et al, 2022, p. 2). On Wikidata, much of the work to populate fields is conducted by bots.…”
Section: Data Labormentioning
confidence: 99%
See 2 more Smart Citations
“…Working on Wikidata, for example, is constrained by database and ontology logics. In contrast, Wikipedia work “is constrained by meeting Wikipedia’s standards for formatting, quality, notability, neutrality, citations, etc., and the results are viewed primarily by humans” (Zhang et al, 2022, p. 2). On Wikidata, much of the work to populate fields is conducted by bots.…”
Section: Data Labormentioning
confidence: 99%
“…Most of the work to populate content on Wikipedia is conducted by human editors, even though many tasks are performed by bots (Geiger & Halfaker, 2017). Zhang et al (2022) thus classify two types of Wikidata workers: Architects and Masons, who differ on their level of desired cognitive engagement, their preference for collaboration or solo work, and their degree of domain expertise. Whereas Architects develop the ontological infrastructure, “modeling and proposing properties,” Masons “perform data entry work [.…”
Section: Data Labormentioning
confidence: 99%
See 1 more Smart Citation
“…While reviewing the literature, it was found that the majority of existing research focuses on either technological aspects or ontological aspects of the platform. More Specifically, review of the literature illustrated that researchers use Wikidata to conduct new types of research (Amaral et al, 2021;Colla et al, 2021;Ferradji & Benchikha, 2021;Good et al, 2016;Kaffee, 2016;Konieczny & Klein, 2018;Lemus-Rojas & Odell, 2018;Li et al, 2022;Meier, 2022;Mietchen et al, 2015;Morshed, 2021;Neelam et al, 2022;Rasberry & Mietchen, 2021;Shenoy et al, 2022;Taveekarn et al, 2019;Waagmeester et al, 2020Waagmeester et al, , 2021Zhang et al, 2022). Researchers also use Wikidata to conduct new types of academic analysis in a variety of disciplines (Arnaout et al, 2021;Burgstaller-Muehlbacher et al, 2016;Kaffee et al, 2017;Klein et al, 2016;Lemus-Rojas, n.d.;Pfundner et al, 2015;Putman et al, 2017;Rutz et al, 2021;Scharpf et al, 2021a, b;Turki et al, 2019Turki et al, , 2022a.…”
Section: Wikidata Users and Early Adoptersmentioning
confidence: 99%